Respuesta :

Answer:

(4,5)

Step-by-step explanation:

To begin, we'll solve for y in the first equation.

-y = 3 - 2x

y = 2x - 3

Then, plug this in for y in the second equation.

9x - 6(2x-3) = 6

9x - 12x + 18 = 6

-3x = -12

x = -12/-3

x = 4

Then, you just plug your x value into one of the equations and solve for y. Personally, I think it's easiest to plug it into y = 2x - 3

y = 2(4) - 3

y = 8 - 3

y = 5

[tex]\bold{\huge{\purple{\underline{ Solution }}}}[/tex]

[tex]\bold{\underline{ Given:-}}[/tex]

  • We have given two equations that is 2x - y = 3 and 9x - 6y = 6

[tex]\bold{\underline{ Let's \: Begin :-}}[/tex]

[tex]\sf{ 2x - y = 3 ...eq( 1 )}[/tex]

[tex]\sf{ 9x - 6y = 6 ...eq( 2 )}[/tex]

Solving eq( 1 ) :-

[tex]\sf{ 2x - y = 3 }[/tex]

[tex]\sf{ x = 3 + y/2 ...eq(3 )}[/tex]

Subsitute eq( 3 ) in eq( 2) :-

[tex]\sf{ 9(3 + y/2) - 6y = 6}[/tex]

[tex]\sf{ 27 + 9y/2 - 6y = 6}[/tex]

[tex]\sf{ 27 + 9y - 12y/2= 6}[/tex]

[tex]\sf{ 27 + - 3y = 6 × 2 }[/tex]

[tex]\sf{ - 3y = 12 - 27 }[/tex]

[tex]\sf{ - 3y = - 15 }[/tex]

[tex]\sf{ y = -15/-3}[/tex]

[tex]\sf{ y = 5 }[/tex]

[tex]\sf{\red {Thus, \: the\: value\: of \:y \: is\: 5 }}[/tex]

Now, Subsitute value of x in eq( 3) :-

[tex]\sf{ x = 3 + 5/2 }[/tex]

[tex]\sf{ x = 8/2 }[/tex]

[tex]\sf{ x = 4}[/tex]

[tex]\sf{\pink{Hence , \: the\: value\: of\:x\:and \:y \: is\: 4 \: and \: 5 .}}[/tex]